Cord blood delta neutrophil index values of term neonates - Büyükeren, Melek; Çelik, Hasan Tolga; Portakal, Oytun; Fadıloğlu, Erdem; Örgül, Gökçen; Yiğit, Şule; Beksaç, M. Sinan; Yurdakök, Murat (The Turkish Journal of Pediatrics, 2020)
In this study, we aimed to demonstrate cord blood immature granulocyte (IG) count and delta neutrophil index (DNI) values for term neonates. This retrospective study consisted of 126 term newborns born between July 2017 and December 2017. Cord blood samples were collected during delivery and IG count together with DNI values were obtained. `Beckman Coulter DXH800 System Hematology Analyzer` was used for analysis and calculations. The median DNI value was found to be 1.0 (interquantile range(IQR) 0.5-1.8%) and the median gestational age at delivery was 38.4 (IQR 37.6-39.0) weeks. The median birth weight and IG count were 3250 (IQR 2955-3593) g and 66 (IQR 26.5-112.3)/mm3, respectively. In conclusion, we believe that determining the normal laboratory reference values of IG count or DNI, which are important potential diagnostic markers for neonatal sepsis, will contribute to future studies on the diagnosis of neonatal sepsis.
Keywords: cord blood; delta neutrophil index; immature granulocyte ratio; neonatal sepsis; neonate